Persepsi Pegawai Terhadap Pelaporan SPT Tahunan Dengan Menggunakan E-Filing - Eferyn, Krissantina; prasaja, Mukti; Riningsih, Dwi (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this study was to determine the effect of employee perceptions on annual SPT reporting using E-Filing. This research is a quantitative study, namely research that emphasizes statistical analysis in testing its hypotheses. Data obtained by using a questionnaire or questionnaire with a population of people from the University of Kediri with a sample of 32 people with a random sampling technique. Then the data is processed and analyzed using simple linear regression techniques to find the relationship between the two variables. The results showed that there was a significant influence between government employees on the use of E-filing in the annual SPT reporting. The influence in this study is positive, meaning that the increase in employee perceptions, the higher the employees are in using this e-filing application.